Rwanda : Fourth Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria: Staff Report; Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Rwandan economy continued to grow strongly in 2011, and significant progress in poverty reduction has been achieved. The Fourth Review Under the Policy Support Instrument (PSI) highlights that the fiscal framework for 2012/13 is in line with the main objectives of the PSI, and the authorities are committed to delay non-priority spending rather than resort to additional domestic financing if revenue collections fall short of target. Efforts are ongoing to further strengthen public financial management and enhance revenue administration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet